Avaliação deflectométrica e de rigidez: estudo de caso em três trechos monitorados em Santa Maria/RS - Bueno, Lucas Dotto (2016)
It is unusual practice, in national projects of new pavements and restorations, the consideration of viscoelastic behavior and non-linear elastic of materials that compound or will compound the layers of pavement. However, the linear elastic response is a simplification of the actual behavior of the pavements layers, since the materials used in the structure have dependent stiffness of the stress state (granular layers and subgrades) or temperature and load application time (asphalt concrete). Therefore, it was aimed to study the behavior of the pavements structures of three monitored sections in the city of Santa Maria/RS. For this, tests were performed with the equipment FWD applying four different loads in each stake that compounds the extension of the three sections. It was found from deflection basins and backcalculated resilient moduli the nonlinear elastic behavior of granular layers (base and sub-base) of the sections 1 and 2, with resilient modulus directly proportional to the increase of the confining pressure. The subgrades of both sections exhibited varied behavior and can be simplified by the linear elasticity without considerable loss. The same happened to the asphalt concrete of section 1. On the other hand, the coating of the section 2 resulted in resilient modules dependent of the increase of vertical surface tension in the center of the load plate. In relation to section 3, the results related only to deflection measures indicated mostly behavior near of linearity in all evaluated reading distances, except for that carried out under the load application. Sequentially to load pulses, also were determined deflections with the Benkelman beam, aiming to find a local correlation between the results obtained from different equipments. The deflections basins indicated higher values, measured with the beam, in relation to those determined by FWD. Consequently, the resilient modules were higher when determined from the backcalculation of the readings taken with FWD, in relation to Benkelman beam. In parallel, it was verified and quantified the influence of bounding conditions between the layers and correction, total or partial, of deflections basins, depending on the temperature, in backcalculated resilient moduli. It was found that the assignment of total bounding in the interfaces between the layers reduces considerably the backcalculated resilient moduli of granular materials. Regarding to the temperature correction, it is appropriate the determination of the rigidity of the granular materials and the subgrade by performing backcalculation without any adjustment in the field basins. Taking these values as a basis, it was considered appropriate to repeat the iterative procedure, with adjustment of the deflections depending on the temperature in the initial readings, thereby determining the new asphalt concrete resilient moduli.